Salt-dependent intermolecular interactions of hyaluronan molecules mediate the formation of temporary duplex structures - Kolaříková, Alena; Kutálková, Eva; Buš, Václav; Witasek, Roman; Hrnčiřík, Josef; Ingr, Marek (Carbohydrate polymers, 2022)
Hyaluronic acid (HA) is a natural polysaccharide present in the connective tissues of vertebrates, often used in the cosmetics and pharmaceutical industries. HA is a strongly hydrophilic macromolecule forming highly swollen random coils in aqueous solutions. Although some authors reported the secondary and tertiary structures of HA chain, others brought convincing evidence contradicting this hypothesis. This study aims at investigation of the stability and dynamics of the temporary duplex HA structures at different NaCl concentrations by molecular-dynamics (MD) simulations. The tendency to duplex formation grows with NaCl concentration reaching its maximum at 0.6 M. This profile is a result of two counteracting NaCl-concentration dependent phenomena, the growing electrostatic-repulsion screening on one side and the disturbance of hydrogen-bonds formation on the other side. Although the weak intermolecular attraction cannot lead to long-lived secondary and tertiary structures, it may influence the properties of large HA macromolecules and concentrated HA solutions.
Keywords: chlorid sodný; Animals; Hyaluronic Acid; Molecular Dynamics Simulation; voda; Sodium Chloride; Water; zvířata; simulace molekulární dynamiky; kyselina hyaluronová; Static Electricity; statická elektřina